Kecepatan Meleleh Dan Organoleptik Es Krim Dengan Penambahan Sari Biji Kluwih Dan Daun Cincau - Hidayah, Atikah Nur, Dra. Suparti, M.Si (2016)
Ice cream with the addition of juice kluwih seeds and leaves of grass jelly is one of the innovations to improve the quality of the ice cream in the food sector. Kluwih seed has sufficient nutrition complete so that it can be used as an alternative additives that can improve the quality of ice cream. Their relatively high chlorophyll content in the leaves to make leaf grass jelly can be used as a natural coloring agent in the manufacture of ice cream. This research aimed to determine speed of melting and organoleptic ice cream with the addition of juice kluwih seeds and grass jelly leaf. This research method using a completely randomized design (CRD) with two factors. The first factor is the addition of juice kluwih seed (S), namely juice kluwih seed 70 ml (S1), juice kluwih seed 75 ml (S2), and juice kluwih seed 80 ml (S3). The second factor is the addition of leaves of grass jelly (D) which leaves grass jelly 7 g (D1), leaves of grass jelly 9 g (D2), and the leaves of grass jelly 11 g (D3). Descriptive data analysis using quantitative and qualitative. The results showed the speed of melting ice cream at the latest on S3D3 treatment, while the speed of the fastest melting ice cream on the treatment S1D1. Organoleptic test results are most appreciated by the public is in treatment S2D2 with a light green color, fairly typical flavour of biji kluwih, sweetness, and soft texture.